Erythrokeratoderma Variabilis - Bedi Gursharan K; Kanwar Amrinder J; Thami Gurvinder P (Wolters Kluwer Medknow Publications, 1999)
Erythrokeratoderma variabilis in an infant is described with classical clinical picture and histopathological changes. Treatment with combination of topical retinoids and steroids was observed to be effective.